The Influence of Parental Engagement on the Early Childhood Learning Process in the Classroom - Mawardi, Khosyim; Oktari, Rici; Sugiarta, I Wayan Arif; Abnisa, Almaydza Pratama (Al Tahdzib: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
Early childhood education forms the foundation of child development through play and parental support. Parental engagement, especially in the form of academic expectations, is essential for children's school readiness and optimal development. This study aims to examine the effect of parental engagement on the classroom learning process of early childhood students at Tunas Bangsa Early Childhood Education, Tanjung Sari II, Palembang. This quantitative research used questionnaires distributed to 24 respondents, with hypothesis testing conducted through a t-test. The results showed that parental engagement in early childhood learning was relatively high, with a mean score of 32.71 and a standard deviation of 3.56. Several indicators, such as parental participation and interaction, were categorized as very high, although aspects of creativity and learning stimulation still require improvement. The regression t-test analysis indicated a significant effect, with a significance value of 0.000 and a regression coefficient of 0.512. The R Square value of 0.537 indicates that parental engagement explains 53.7% of the variance in learning outcomes. Conclusion: Parents have a strong influence in supporting early childhood learning in the classroom.